Left ventricular morphology in patients with aortic coarctation and bicuspid aortic valve: novel insights from a statistical shape modelling framework. (3rd October 2022) - Sophocleous, F; Standen, L; Doolub, G; Laymouna, R; Bucciarelli-Ducci, C; Caputo, M; Manghat, N; Hamilton, M; Curtis, S; Biglino, G
Abstract: Background: The functional implications of left ventricular (LV) morphological characterization in congenital heart disease (CHD) are not widely explored. Purpose: This study qualitatively and quantitatively assessed LV shape associations with a) LV function and b) thoracic aortic morphology in patients with aortic coarctation (CoA) with/without bicuspid aortic valve (BAV). Methods: A statistical shape modelling (SSM) framework was employed to analyse three-dimensional (3D) LV shapes from cardiac magnetic resonance (CMR) imaging data in n=110 cases including: isolated CoA (n=25), CoA+BAV (n=30), isolated BAV (n=30), and age-matched healthy controls (n=25). Average 3D templates (Picture 1) and deformations were computed. Correlations between shape data and CMR-derived morphometric parameters (i.e. sphericity, conicity) as well as CMR-derived global and apical strain values were assessed to elucidate possible functional implications. The relationship between LV shape features and arch architecture (i.e. gothicity, tortuosity) was also explored by means of regression analysis. Results: The LV template was shorter and more spherical in CoA patient (Picture 1), as also confirmed by statistical analysis of the SSM-derived shape modes. LV sphericity, which was higher in CoA, was associated (p≤0.04) with lower global longitudinal, radial and circumferential strain, irrespective of the presence of aortic stenosis and/or regurgitation. Conversely, neither LV morphology nor LV strain was not associated with arch architecture. Conclusions: Differences in LV morphology were observed between CoA and BAV patients. Increasing LV sphericity was associated with reduced strain, independent of aortic arch architecture and functional aortic valve disease. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation and NIHR BRC